Corrosion behaviour of waste disposal container in sub-surface disposal system. (September 2014) - Waki, T.; Nakagami, M.; Wada, H.; Ooma, T.; Kato, O.; Kinugasa, J.
<x content-type="archive" xml:space="preserve">Abstract</x> This study was conducted in order to clarify the long term corrosion behaviour of containers made of carbon steel. Natural immersion crevice corrosion tests were carried out for 360 days in an alkaline and reducing environment using a combination of materials including carbon steel and welding materials or bolts. In addition, potentiostatic crevice corrosion tests were carried out for 90 days. In both tests, there was no evidence to suggest localised corrosion in the different kinds of metal contact parts, including carbon steel, welding materials and bolts. It was also recognised that crevice corrosion was less likely to be generated on disposal container materials. From these experimental results, it is believed that the possibility of localised corrosion is extremely low if the environment around the carbon steel container is maintained under highly alkaline and reducing conditions.